Efektivitas Younger Dalam Menurunkan Emesis Gravidarum Pada Ibu Hamil Trimester I Di Kota Samarinda - Yusuf, Nuuva; Saidah, Siti; Amalia, Vidia Rizki; Nada, Nada; Fitri, Isyah Aprilya Nur (Bunda Edu-Midwifery Journal (BEMJ), 2023)
During pregnancy, there are usually many complaints or discomfort that usually occur. One of them is emesis gravidarum that occurs in first timester pregnant women. One effort to overcome emesis gravidarum complaints is tocombine prenatal yoga with ginger aromatherapy. The results showed that the p value was 0.000 less than 0.05, meaning prenatal yoga and ginger aromatherapy were effective for treating emesis gravidarum in pregnant women. It is hopedthat this research can be used as input and evaluation in providing antenatal care service to overcome emesis gravidarum complaints in pregnant women.